B324 Erector spinae plane block for robot-assisted minimally invasive direct coronary artery bypass surgery: a double-blind, prospective randomized placebo-controlled trial. (11th August 2022) - Hoogma, DF; van den Eynde, R; Oosterlinck, W; Al tmimi, L; Tournoy, J; Verbrugghe, P; Fieuws, S; Coppens, S; Rex, S
Abstract : Background and Aims: Thoracotomy for robot-assisted minimally invasive direct coronary artery bypass (RAMIDCAB) surgery may cause severe early postoperative pain. 1 The Erector Spinae Plane (ESP) block may be an effective and safe option for postoperative analgesia in RAMIDCAB surgery. 2 As randomized trials in this field are lacking, 3 we investigated ifin RAMIDCAB surgery, intermittent ESP block adjuvant to the standard multimodal analgesic regimen, compared to solely the latter, is effective in reducing postoperative pain. Methods: This single center, double-blind, prospective, randomized, placebo-controlled trial was approved by the Ethics Committee of the University Hospitals Leuven, Belgium (DH 11–2018 Version 008 26–10-2020 – EudraCT 2019–000596-16). The trial was supported by an ESRA Research Grant 2019. Between May 15th2019 and July 4th2021, 64 patients undergoing RAMIDCAB surgery were randomized to postoperatively receive an ESP catheter with either intermittent ropivacaine 0.5% (ropi-group) or normal saline 0.9% (placebo-group). Primary endpoint was postoperative 24h morphine consumption. Multiple secondary endpoints were evaluated up to 30-days postoperatively. Results: The median (IQR) 24h morphine consumption was not different between the ropi- and placebo-group: 67mg (35;84) vs 71mg (52;90), p=0.25. Mean numerical rating scale values for pain showed no significant difference between the groups ( Figure 1 ). The number of morphine-boluses requested each hour by the patient and other secondary outcomes were comparable, figure 2 and table 1, respectively. Conclusions: In the current study, adding an ESP-block to a standard multimodal analgesia regimen did not result in reduced morphine consumption after RAMIDCAB surgery.